Climate stress tests, bank lending, and the transition to the carbon-neutral economy - Larissa Fuchs; Huyen Ngyuen; Trang Nguyen; Klaus Schaeck (Halle Institute for Economic Research (IWH), 2024)
We ask if bank supervisors' efforts to combat climate change affect banks' lending and their borrowers' transition to the carbon-neutral economy. Combining information from the French supervisory agency's climate pilot exercise with borrowers' emission data, we first show that banks that participate in the exercise increase lending to high-carbon emitters but simultaneously charge higher interest rates. Second, participating banks collect new information about climate risks, and boost lending for green purposes. Third, receiving credit from a participating bank facilitates borrowers' efforts to improve environmental performance. Our findings establish a hitherto undocumented link between banking supervision and the transition to net-zero.
Keywords: G21; G28; K11; 330; banking supervision; carbon risk; climate stress test; green finance; syndicated loans